MODEL EFEKTIVITAS TATA KELOLA MELALUI SKEMA STAKEHOLDER DYNAMICS DESA AGROWISATA NGLINGGO - Astono, Anjar Dwi; Indriani, Sekarlita; Parlindungan, Davis Roganda; Hutapea, Michael Supriady; Gunawan, Vincent Louis; Ardianto, Marcelinus Bily (Universitas Multimedia Nusantara, 2023)
Abstract- Despite Nglinggo Village's initiative in agrotourism development, challenges persist in its governance. The research's novelty lies in its examination of agrotourism through the prism of stakeholder dynamics, amalgamated with the innovation for sustainability strategy concept. Employing a qualitative approach within the constructivist paradigm, the study unravels the intricacies of issues within the tea plantation agrotourism of Nglinggo Tourist Village, Samigaluh, Yogyakarta. Findings underscore critical success factors for effective governance, including community participation, environmental sustainability, quality services, and stakeholder management. In conclusion, a comprehensive model integrated into the Nglinggo Tourist Village Tea Plantation Agrotourism development framework is essential, comprising phases such as preparation, development, implementation, and evaluation. This model ensures ongoing reevaluation by all Keywords: Agrotourism Planning; Economy; Implementation Outcomes; Nature